(untitled) (Research, Society and Development, 2026)
Dental trauma represents a significant public health concern, particularly among children and adolescents, with tooth avulsion being considered one of the most severe traumatic dental injuries. Delayed replantation is associated with an unfavorable prognosis and is frequently related to pulp necrosis, ankylosis, and external root resorption, often leading to the premature loss of the affected tooth. The present study aims to report the clinical management of a case of traumatic avulsion of the maxillary central incisors (11 and 21) in a 10-year-old patient who underwent delayed replantation and subsequently developed severe external root resorption. This study is a retrospective clinical case report. The treatment approach consisted of intracanal alkalinization through the use of calcium hydroxide as intracanal medication, followed by the placement of a bioceramic material for definitive sealing, aiming to reduce clastic activity and delay the progression of the resorptive process. The patient remains under periodic clinical and radiographic follow-up to evaluate tooth stability, the presence of infectious signs, mobility, and the progression of resorption. After approximately one year of follow-up, stabilization of the resorptive process was observed, with no clinical signs of infection or tooth mobility. It can be concluded that conservative approaches based on intracanal alkalinization associated with the use of bioceramic materials may represent a viable therapeutic alternative to delay the progression of root resorption in late replanted teeth, contributing to the functional and aesthetic maintenance of the teeth during the patient’s growth period.